Employees' online knowledge sharing: the effects of person-environment fit. Issue 2 (3rd April 2017) - Pee, L.G.; Min, Jinyoung
Abstract : Purpose: Various individual and environmental factors influencing employees' online knowledge sharing have been identified, but the understanding regarding these has been mostly limited because of their independent and direct effects our understanding has been mostly limited to their independent and direct effects. This study aims to propose that the fit between employees and their environments (PE fit) matters. A model explaining how PE fit and misfit affect employees' knowledge sharing behavior through influencing their affective commitment is developed and assessed. Design/methodology/approach: The proposed model was assessed with data collected in a survey of 218 employees. Findings: Results indicate that PE fit in the norm of collaboration, innovativeness and skill variety leads to the development of stronger affective commitment and, therefore, more knowledge sharing behavior than when they are in shortfall or excess in the environment (i.e. PE misfit). Originality/value: The findings indicate a new direction for knowledge sharing research that focuses on PE fit and suggest that knowledge sharing can be improved more proactively in practice by assessing PE fit during recruitment.